Sales, agency and bailments with selected provisions of documentary stamps Executive Order No. 273 (Value-Added Tax Law) and Revenue Regulations, no. 5-87 - Diaz, Virginia M. (Anvil, 2007)
This book is designed primarily for Commerce students. Efforts have been made to make the provisions of the laws on Sales, Agency, and Bailments understandable to the average student who, in the study of the law, has had little or no business experience. HE has difficulty in visualizing the business transactions in which particular provisions of the law are applicable. Certain business settings are created, practical applications are given and recital of some adjudicated cases is made to help guide the student in using his knowledge of the law in arriving at the correct decision. Certain parts of this text deal with the important provisions of Executive Order No. 273 (Value-Added Tax) and the Documentary Stamp Tax, to cover not only the legal aspects but its social aspects as well. Some reorganization of the subject matter has been made to emphasize topics of greater concern which the student will meet for the first time in business or in his initial entrepreneurial activity. This will also make the teacher's task much easier, because the student, realizing the importance of these topics will be motivated to learn the law.